Petroleum depletion scenarios for Australian cities - Wight, W.; Newman, Peter (Federation Press, 2010)
This paper outlines what are the likely global ‘events’ that peak oil could induce in our highly globalised world including supply disruption, volatility in prices and progressive price rises. All these will impact on our cities. We then pose three indicative development scenarios and assess them as a risk management exercise to examine the relative vulnerability of urban development scenarios and what pattern of development will provide the greatest opportunity for responding to this challenge. Finally a ‘glimpse of the future in 2040’ is presented to show how the combination of new technology and good urban planning can enable us to make better cities in the future.